Aktivitas Perilaku Pencarian Nformasi Mahasiswa di UINSU - Putri Asa Parent; Franindya Purwaningtyas; Nuraina Nuraina; Sarida Sinulingga; Sriulina Maha (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Information seeking behavior and information needs are carried out by everyone to fulfill the knowledge they want, including students. Before searching for information students must first know what information they need, such as making a list of information to be searched for, then after making a list of information to be sought, the behavior when searching for information is to start browsing or where to look for that information, after being sure of the source of the information being sought. then students must verify and sort out the information to be retrieved. The method used in this study is a qualitative research method to describe the characteristics of the cases studied. Sulistyo-Basuki (2006: 78) explains that qualitative research aims to obtain a complete picture of a matter from the point of view of the human being studied. In fulfilling the needs of different information, students will do any way to get the information according to their needs. To get the information that suits their needs, UINSU students don't just use one source of information to get the information they need. Keywords: Students, Information Search Behavior, Information Needs